2013
DOI: 10.1158/1078-0432.ccr-12-2897
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus DNA Load in Nasopharyngeal Brushings and Whole Blood in Nasopharyngeal Carcinoma Patients before and after Treatment

Abstract: Purpose: Nasopharyngeal carcinoma (NPC) is consistently associated with Epstein-Barr virus (EBV) and highly prevalent in Indonesia. EBV-DNA load can be used for early diagnosis and may have prognostic value. In this study, EBV-DNA load was evaluated in minimal invasive nasopharyngeal (NP) brushings and whole blood for initial diagnosis and therapy assessment against the standard-of-care diagnosis by biopsy with EBV-RISH and standard EBV-IgA serology.Experimental Design: NP brushings and blood samples were coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 30 publications
12
64
0
Order By: Relevance
“…Post-treatment IgA-EBV serology failed to determine prognostic difference among NPC patients. This is consistent with the previous studies done by Adham et al (2013) and Ai et al (2013). Direct quantification of viral EBV DNA, therefore, might lend a hand to support the notion that viral reactivation play important role in disease progression and survival (Hassen et al, 2011;Wang et al, 2013;Yip et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Post-treatment IgA-EBV serology failed to determine prognostic difference among NPC patients. This is consistent with the previous studies done by Adham et al (2013) and Ai et al (2013). Direct quantification of viral EBV DNA, therefore, might lend a hand to support the notion that viral reactivation play important role in disease progression and survival (Hassen et al, 2011;Wang et al, 2013;Yip et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings was reported by Adham et al (2013) among NPC patients in Indonesia. Adham et al (2013) reported that there was no significant reduction at 2-months post-treatment of IgA EBV either IgA EBNA1 or IgA VCA-p18.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, EBV DNA levels return to normal levels after successful radiotherapy; persistently raised EBV DNA levels may indicate a poor outcome after therapy. 49,50 While there is still no direct evidence, it has been suggested that the source of plasma EBV DNA is apoptotic cancer cells which are shed into the blood stream or circulating cancer cells as they migrate to distant sites to cause metastasis. 27 While the plasma EBV DNA which originates from apoptotic or detached circulating tumor cells is a valuable marker for NPC, it is possible that new EBV biomarkers which are associated with actively growing cancer cells may provide a new approach for evaluation of the presence of NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…EBV-DNA may be detected in NPC cells (5,6), and cell-free EBV-DNA may be detected in the plasma of patients with NPC (7)(8)(9)(10)(11)(12)(13). Furthermore, the levels of plasma EBV-DNA in recently diagnosed NPC patients have been significantly correlated with tumor volume (14,15), response to treatment (16), tumor clearance (17,18) and tumor recurrence (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%